From Minds to Markets - Gruber, Marc; MacMillan, Ian C.; Thompson, James D. (Journal of Management, 2012)
The resource-based view suggests that firms’ heterogeneous resource endowments are important for explaining interfirm performance differences. To date, however, the literature provides little insight on the factors that shape the identification of markets in which firm resources, as embodied in a product or service, can create value for end customers. Building on entrepreneurship research and Penrose’s early resource-based work, the authors examine how four main types of pre-entry human capital endowments (i.e., the characteristics that the founders bring to the founding process) shape the identification of market opportunities for emerging technology firms. They find that prior entrepreneurial and management experience endowments enhance, while marketing and technological experience endowments constrain, the number of market opportunities identified. In addition, the authors find that the number of market opportunities identified depends on the combinations of generalized and specialized endowments in the founding team.